Detección y cuantificación del potato mop-top virus (pmtv) en colombia mediante qrt-pcr (2013)
Potato mop-top virus (PMTV) is a re-emerging virus in potato crops in Colombia. It is transmitted by Spongospora subterranea, the causal agent of Powdery scab. Detection of PMTV is difficult due to its irregular distribution in infected plants, low titer and systemic movement of naked RNA. To increase the number of diagnostic tools available to detect the PMTV strains present in Colombia and to support seed certification schemes, a two-step qRT-PCR test using primers PMTV-1948F/ PMTV-2017R and the Taqman® probe PMTV-1970 targeted to the CP-RT gene of RNA2 from PMTV was evaluated. A standard curve was obtained from in vitro transcripts of a 1513 pb fragment of this gene. The qRT-PCR test was evaluated using Nicotiana benthamiana and Solanum phureja bait plants inoculated with Sss cystosori, root-tissue from plants of potato showing symptoms of Powdery scab in La Unión (Antioquia, Colombia) and commercial tuber seeds. qRT-PCR was able to detect PMTV from roots in 11 out of 20 bait plants; while in the case of field samples 14 out 15 plants tested positive with concentration between 4,72x1011-7,60x1013 viral particles/μL. Finally, PMTV was detected in one out of 16 tuber seeds tested. These results demonstrate that qRT-PCR can be used routinely in the detection of PMTV strains affecting potato in Colombia.